Analysis of Designs and Performance of Existing Greenhouse Solar Dryers in Kenya - Ndirangu, S N; Kanali, C L; Mutwiwa, U N; Kituu, G M; Ronoh, E K (Journal of Postharvest Technology, 2018)
Solar drying offers a convenient, cheaper and environmentally friendly way to dry food. In Kenya, solar dryers have been developed and  introduced by different actors. However, their technical and economic performance is unknown. This study assessed the technical  performance of existing greenhouse dryers in Kenya, by focusing on their design, use and performance. The data was further analysed to  identify the correlation between identified parameters. The study was conducted in parts of Eastern and Central regions in Kenya. A total of 18  dryers were sampled from 50 identified dryers. The average size of greenhouse dryers was 8.12 m long, 3.95 m wide and 2.37 m high. The  study also analysed designers, selection of construction, internal configuration, and cost of dryers. Generally, a good consideration was noted  in these aspects. 24% of dryers experienced losses over 10%. Major causes of losses were cold weather, spillage and poor ventilation. Most  dryers achieved good quality products, with 29% getting less than 50% of grade 1. On average, the drying rate was 13, 56, 48 and 64 hours  for mangoes, bananas, cassava and butternut, respectively. These drying rates relate well with other studies. Overall, correlation analysis  showed consistence in dryer design, use and performance.
Keywords: Analysis; design,; greenhouse dryers; Kenya; performance